2022
DOI: 10.1039/d2sc00256f
|View full text |Cite
|
Sign up to set email alerts
|

An open source computational workflow for the discovery of autocatalytic networks in abiotic reactions

Abstract: A central question in origins of life research is how non-entailed chemical processes, which simply dissipate chemical energy because they can do so due to immediate reaction kinetics and thermodynamics,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 97 publications
0
16
0
Order By: Relevance
“…Various constraints can be imposed on the rule set to ensure that the generated reaction network is specific and not a generalized combinatorial set of all possible graphs, i.e., it accurately represents real-world chemistry. We note that previous applications of these methods, even using 200 AMU expansion cutoffs, manage to faithfully reproduce diverse product suites detected in real world chemistry, match high-resolution mass spectra of real reactions, and faithfully predict trends in real chemistry-derived Van Krevelen and Kendrick plots [20], attesting to these methods' ability to predict real world chemistry. We briefly review the use of these methods here, more complete information can be found in [20].…”
Section: Reaction Network Generationmentioning
confidence: 70%
See 3 more Smart Citations
“…Various constraints can be imposed on the rule set to ensure that the generated reaction network is specific and not a generalized combinatorial set of all possible graphs, i.e., it accurately represents real-world chemistry. We note that previous applications of these methods, even using 200 AMU expansion cutoffs, manage to faithfully reproduce diverse product suites detected in real world chemistry, match high-resolution mass spectra of real reactions, and faithfully predict trends in real chemistry-derived Van Krevelen and Kendrick plots [20], attesting to these methods' ability to predict real world chemistry. We briefly review the use of these methods here, more complete information can be found in [20].…”
Section: Reaction Network Generationmentioning
confidence: 70%
“…We note that previous applications of these methods, even using 200 AMU expansion cutoffs, manage to faithfully reproduce diverse product suites detected in real world chemistry, match high-resolution mass spectra of real reactions, and faithfully predict trends in real chemistry-derived Van Krevelen and Kendrick plots [20], attesting to these methods' ability to predict real world chemistry. We briefly review the use of these methods here, more complete information can be found in [20]. This pipeline is open-source, written mostly in Python, and can be accessed along with relevant documentation at https:// github.com/Reaction-Space-Explorer/reac-space-exp (accessed on 10 July 2021).…”
Section: Reaction Network Generationmentioning
confidence: 70%
See 2 more Smart Citations
“…Given the absence of empirical evidence for the nature of environments and chemistry on the prebiotic Earth, we envisage that data integration accounting for interference effects will at some level rely on linked simulations. Progress is this regard being made in several relevant areas, including the formulation of selfconsistent global biogeochemical models, which are being employed to reconstruct the evolution of Earth's surface environment over time (Lenton et al, 2018;Mills et al, 2018), and rule-based models of complex chemical systems in the modelling of physical chemistry (Goldford et al, 2019;Wołos et al, 2020;Arya et al, 2022). We view these tools as being likely essential for bridging spatial and timescales that are not tractable in the lab and for linking fields (e.g., feeding simulations of prebiotic systems into models of planetary geochemistry).…”
Section: Data Collection Versus Integrationmentioning
confidence: 99%